2012
DOI: 10.2196/jmir.2016
|View full text |Cite
|
Sign up to set email alerts
|

Clinicians’ Expectations of Web 2.0 as a Mechanism for Knowledge Transfer of Stroke Best Practices

Abstract: BackgroundHealth professionals are increasingly encouraged to adopt an evidence-based practice to ensure greater efficiency of their services. To promote this practice, several strategies exist: distribution of educational materials, local consensus processes, educational outreach visits, local opinion leaders, and reminders. Despite these strategies, gaps continue to be observed between practice and scientific evidence. Therefore, it is important to implement innovative knowledge transfer strategies that will… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 40 publications
1
30
1
Order By: Relevance
“…Initially it was thought that respondents’ levels of perceived usefulness and intention to use an online community could be covariate, but this was not the case and usefulness was an independent predictor of intention to use an online community. This is in keeping with findings of 2 studies of use and intention to use social media among health care professionals, and previous studies on technology acceptance [20,22,23]. The Technology Acceptance Model was developed to describe the most significant predictors of technology use in the general community.…”
Section: Discussionsupporting
confidence: 61%
“…Initially it was thought that respondents’ levels of perceived usefulness and intention to use an online community could be covariate, but this was not the case and usefulness was an independent predictor of intention to use an online community. This is in keeping with findings of 2 studies of use and intention to use social media among health care professionals, and previous studies on technology acceptance [20,22,23]. The Technology Acceptance Model was developed to describe the most significant predictors of technology use in the general community.…”
Section: Discussionsupporting
confidence: 61%
“…Some health professionals were reported to use social media to collect data on patients [26,65] and to communicate with patients using online consultations [88]; however, this latest use is limited. Recent research reported that female health professionals in Quebec, Canada, believed that Web 2.0 may be a useful mechanism for knowledge transfer but is limited due to their lack of time and technological skills [126]. Perhaps in light of Kaplan and Haenlein’s [10] classifications of social media, further work on improving the “social presence”, the closeness to synchronous face-to-face communication of such online consultations, would contribute to improving communication between health professionals and patients.…”
Section: Discussionmentioning
confidence: 99%
“…Most published studies have shown that teleconsultation and data transfer are limited to primary care physicians and specialists, without allowing other professionals to get involved. In this context, the creation of communities of clinical practice has proven to be a useful means of solving problems and improving the functioning of healthcare organisations [11, 12]. …”
Section: Discussionmentioning
confidence: 99%
“…However, according to the both systematic reviews [10] and [11], there is still little evidence to show whether the use of communities of practice, which rely heavily on social network and information and communication technology use, actually leads to improved efficiency in the integration across primary and hospital care services [12]. …”
Section: Introduction Comprising Background and Problem Statementmentioning
confidence: 99%